Impact of Quality of Work Life on the Organizational Effectiveness at Military Hospitals in Riyadh Region from Employees’ Perspective - AlHashimi, Riyad; Adayleh, Ali (Jordan Journal of Business Administration, 2017)
This study aims at identifying the level of quality of work life and its impact on the organizational effectiveness at the military hospitals in Riyadh, Saudi Arabia, from the perspective of employees. The study used the descriptive method. A sratified random sample of employees at these hospitals was chosen. 450 questionnaires were distributed, of which 403 were answered back (89.9%) and were valid for statistical analysis. After statistical analysis of data using SPSS program, the study reached some findings, the most important of which are: the quality of work life from the perspective of the employees at military hospitals is at medium level, with an average point of (3.18). From the perspective of the employees, the organizational effectiveness at military hospitals is medium, with an average point of (3.26). The findings revealed statistically significant differences in the surveyed employees’ perceptions of quality of work life with regards to the demographic variables of (nationality and experience), where results came in favor of non-Saudis and employees with less than 6 years of experience. The results showed no statistically significant differences in the perceptions of respondents to the quality of work life attributable to variables of (hospital, age, education, marital status, category, rank / occupation and gender). The study recommends setting a clear and appropriate promotion system in order to ensure implementation of the objectives of the hospitals and aspirations of their employees, as well as paying attention to improving the work environment and conditions at military hospitals and putting into effect flexible work schedules for the interest of military hospitals and their employees.